Handbook of Epidemiology: with 180 tables - Ahrens, Wolfgang; Pigeot, Iris (Springer, 2005)
The Handbook of Epidemiology provides a comprehensive overview of the field and thus bridges the gap between standard textbooks of epidemiology and dispersed publications for specialists that have a narrowed focus on specific areas. It reviews the key issues and methodological approaches pertinent to the field for which the reader pursues an expatiated overview. It thus serves both as a first orientation for the interested reader and as a starting point for an in-depth study of a specific area as well as a quick reference and recapitulatory overview for the expert. The book includes topics that are usually missing in standard textbooks and that are only marginally represented in the specific literature as well as innovative areas, e.g. molecular epidemiology, ethical aspects, practical field work, health systems research, quality control, and good epidemiological practice. Each chapter is written by one or more leading scientists and represents the state-of-the-art knowledge. TOC:Section 1: Concepts and Methodological Approaches in Epidemiology.- Section 2: Statistical Methods in Epidemiology.- Section 3: Applications in Epidemiology.- Section 4: Research Areas in Epidemiology
Keywords: Epidemiologie